Exploring the epidemiological burden of RSV pre- and post-COVID-19 pandemic: A Jordanian tertiary hospital experience - Enas Al-Zayadneh; Dana Marie; Farah A. Khraisat; Suzan S. Musa; Jehad Feras AlSamhori; Dina Alkhateeb Altamimi; Alia O. Khashman; Amirah Daher; Montaha AL-Iede (Journal of International Medical Research)
Objectives To describe changes in respiratory syncytial virus (RSV) epidemiology, its associated clinical outcomes and predictors of severe acute lower respiratory tract infection (ALRTI) pre- and post-COVID-19. Methods In this retrospective cohort, we analysed data from electronic medical record of children <5 years who were hospitalized at Jordan University Hospital with RSV-associated ALRTI from 2018 to 2022. Results 325 inpatients with respiratory infections were included. Rate of RSV infections decreased from 74% pre-pandemic to 30% post-pandemic. Patients diagnosed with ALRTI post-COVID had significantly higher SpO2, less chronic disease, lower temperature and respiratory rate at admission and fewer days in hospital compared with those diagnosed pre-COVID. Furthermore, patients diagnosed pre-pandemic were significantly more likely to have abnormal X-rays, used more antibiotics and antivirals, and had higher rates of severe disease than those with infection post-COVID. Conclusion COVID-19 and its associated social restriction measures led to changes in RSV epidemiology, characterized by a decline in rates and clinical severity in the post-pandemic period. However, further studies are needed to characterize the impact of COVID-19 on subsequent RSV seasons.